Sensitization of ovarian cancer cells to cisplatin by genistein: the role of NF-kappaB - Solomon Leigh A; Ali Shadan; Banerjee Sanjeev; Munkarah Adnan R; Morris Robert T; Sarkar Fazlul H (BMC, 2008)
Abstract Background Platinum-resistance (PR) continues to be a major problem in the management of epithelial ovarian cancer (EOC). Response to various chemotherapeutic agents is poor in patients deemed PR. Genistein, a soy isoflavone has been shown to enhance the effect of chemotherapy in prostate and pancreatic cancer cells in vitro and in vivo by reversing chemo-resistance phenotype. The goal of this study was to investigate the effects of combination therapy with genistein and cisplatin as well as other cytotoxic conventional chemotherapeutic agents in platinum-sensitive (PS) and resistant EOC cells. Methods The PS human ovarian cancer cell line A2780 and its PR clone C200 cells were pretreated with genistein, followed by the combination of genistein and either cisplatin, taxotere or gemcitabine. Cell survival and apoptosis was assessed by MTT and histone-DNA ELISA. Electrophoretic mobility shift assay (EMSA) was used to evaluate NF-κB DNA binding activity. Western blot analysis was performed with antibodies to Bcl-2, Bcl-xL, survivin, c-IAP and PARP. Results Reduction in cell viability, and corresponding induction of apoptosis was observed with genistein pretreatment followed by combination treatment with each of the drugs in both cell lines. The PS cell line was pretreated for 24 hours; in contrast, the PR cell line required 48 hours pretreatment to achieve a response. The anti-apoptotic genes c-IAP1, Bcl-2, Bcl-xL, survivin and NF-κB DNA binding activity were all found to be down-regulated in the combination groups. Conclusion This study convincingly demonstrated that the current strategy can be translated in a pre-clinical animal model, and thus it should stimulate future clinical trial for the treatment of drug-resistant ovarian cancer.